Redefining the role of Broca’s area in speech - Flinker, Adeen (Proc Natl Acad Sci U S A, 2015)
For over a century neuroscientists have debated the dynamics by which human cortical language networks allow words to be spoken. Although it is widely accepted that Broca’s area in the left inferior frontal gyrus plays an important role in this process, it was not possible, until recently, to detail the timing of its recruitment relative to other language areas, nor how it interacts with these areas during word production. Using direct cortical surface recordings in neurosurgical patients, we studied the evolution of activity in cortical neuronal populations, as well as the Granger causal interactions between them. We found that, during the cued production of words, a temporal cascade of neural activity proceeds from sensory representations of words in temporal cortex to their corresponding articulatory gestures in motor cortex. Broca’s area mediates this cascade through reciprocal interactions with temporal and frontal motor regions. Contrary to classic notions of the role of Broca’s area in speech, while motor cortex is activated during spoken responses, Broca’s area is surprisingly silent. Moreover, when novel strings of articulatory gestures must be produced in response to nonword stimuli, neural activity is enhanced in Broca’s area, but not in motor cortex. These unique data provide evidence that Broca’s area coordinates the transformation of information across large-scale cortical networks involved in spoken word production. In this role, Broca’s area formulates an appropriate articulatory code to be implemented by motor cortex.